Sistem Rekomendasi Drama dan Film Berbasis Website Dengan Metode Content Based Filtering - Yusniar; Yolen Perdana Sari (CV. Multi Kreasi Media, 2024)
Developments in the film industry have been very rapid from time to time. Thousands of film and drama titles appear in a year from various genres, players and plots. The recommendation system will assist users in making choices based on the data to be processed. In this study, a drama and film recommendation system will be built using the content-based filtering method with TF-IDF calculations and cosine similarity through data such as title, genre, synopsis and cast so that users can easily search for shows based on the type of drama or film they like.